Education On Consumption of Fe Tablets Increases Hemoglobin Levels Index In Pregnant Women - Sabilla Ratu Cetrin; Evi Wahyuntari; Nuli Nuryanti Zula (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Anemia is a global public health problem that can increase morbidity and mortality rates among mothers and infant. Education about anemia in pregnant women will get good results when using appropriate media. One of the health promotion methods with persuasive visual messaging is through the use of leaflets. The purpose of this study is to determine the effect of education on Fe tablet consumption on the increase of Hb levels index in pregnant women in the Mlati I Public Health Center region. The research method is a quantitative pre-experimental design with a one group pretest posttest design. The population consists of 149 pregnant women with anemia. The sample is 22 individuals selected using non-probability sampling, specifically purposive sampling.  The results of data analysis using wilcoxon test obtains with an asymp. sig (2-tailed) value of 0.001 < 0.05.  There is a significant effect ofeducation using leaflets and supervision of taking Fe tablets using observation sheets that are followed up 3x a week on the consumption of Fe tablets with an increase in hemoglobin levels index. This indicates that there is an influence of education on consuming Fe tablets with an increase Hb levels in pregnant women after intervention 4 weeks.